2013
DOI: 10.1002/oby.20189
|View full text |Cite
|
Sign up to set email alerts
|

Doctor shopping by overweight and obese patients is associated with increased healthcare utilization

Abstract: Negative interactions with healthcare providers may lead patients to switch physicians or “doctor shop.” We hypothesized that overweight and obese patients would be more likely to doctor shop, and as a result, have increased rates of emergency department (ED) visits and hospitalizations as compared to normal weight non-shoppers. We combined claims data from a health plan in one state with information from beneficiaries’ health risk assessments. The primary outcome was “doctor shopping,” which we defined as hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…We only included patients who were actively engaged in primary care, so our population excludes patients who may not be engaged in care due to dissatisfaction or lack of trust in the healthcare system. A prior study found that overweight and obese patients were more likely to “doctor shop” (27), so our results may underestimate the prevalence of patient-perceived weight-related judgment by providers.…”
Section: Discussionmentioning
confidence: 67%
“…We only included patients who were actively engaged in primary care, so our population excludes patients who may not be engaged in care due to dissatisfaction or lack of trust in the healthcare system. A prior study found that overweight and obese patients were more likely to “doctor shop” (27), so our results may underestimate the prevalence of patient-perceived weight-related judgment by providers.…”
Section: Discussionmentioning
confidence: 67%
“…This suggests that the small percentage of patients who see surgery as their best hope may gravitate to surgeons who are more likely to offer it. So-called ''doctor shopping'' has been studied in other fields and has been associated with decreased patient satisfaction and with opioid addiction [9,13]. Future research should focus on factors associated with seeking a second opinion in the field of hand surgery and the influence on final patient symptoms and disability.…”
Section: Discussionmentioning
confidence: 99%
“…It may also result from the GPs’ general qualities such as organizational skills, communication abilities, or empathic attitudes. It has been suggested that such patterns may result from patients’ negative interactions with healthcare providers, so that, for instance, obese patients search for “obese friendly” physicians [25]. Patients could also make use of informal conversations (word-of-mouth) with family, friends, or colleagues that recommend one GP or another, which seems to have a greater effect on the choice of GP than public information disclosure [20].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction between chronically ill patients and their GPs has not been given specific attention in previous literature, but a previous study of obese patients may contain clues for generalizable results: reportedly, obese patients avoided physicians they perceived as sources of stigma and searched for providers who were “obese friendly” [25]. …”
Section: Introductionmentioning
confidence: 99%